SIGNIFICANCE OF PRAGMATIC COMPETENCE AS A STRUCTURAL COMPONENT OF COMMUNICATIVE COMPETENCE (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
Determining the role of pragmatic competence within foreign language communicative competence is reflected in the works of many researchers in the field of linguistics. For a long time, teaching a foreign language involved students mastering only the grammar and vocabulary of the target language. However, with the advent of the communicative approach to teaching a foreign language in the second half of the twentieth century, the need arose to master not only linguistic competence which included only grammar and semantic units as was previously practiced, but also a number of other competencies such as pragmatic competence. Pragmatic competence was underestimated for a long time. This paper provides data about the importance of pragmatic competence as a part of communicative competence.